2007
DOI: 10.1002/adsc.200700010
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric 1,3‐Dipolar Cycloaddition Reaction between α,β‐Unsaturated Aldehydes and Nitrones Catalyzed by Well‐Defined Iridium or Rhodium Catalysts

Abstract: Reaction of the complexes (SM,RC)‐[(η5‐C5Me5)M{(R)‐Prophos}(H2O)](SbF6)2 (M=Rh, Ir) with α,β‐unsaturated aldehydes diastereoselectively gave complexes (SM,RC)‐[(η5‐C5Me5)M{(R)‐Prophos}(enal)](SbF6)2 which have been fully characterized, including an X‐ray molecular structure determination of the complex (SRh,RC)‐[(η5‐C5Me5)Rh{(R)‐Prophos}(trans‐2‐methyl‐2‐pentenal)](SbF6)2. These enal complexes efficiently catalyze the enantioselective 1,3‐dipolar cycloaddition of the nitrones N‐benzylideneaniline N‐oxide and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Enantioselective approaches involving transition metal catalysts have been successful with bidentate dipolarophiles such as those derived from oxazolidinones that provide two-point binding to the chiral Lewis acid [98]. However, there have been few examples of highly selective 1,3-dipolar cycloaddition reactions with α,β-unsaturated aldehydes that are monodentate dipolarophiles [8,[99][100][101][102], and those using methacrolein have shown greater selectivities than those with acrolein. A clear understanding of factors that influence reactivity and selectivity in nitrone cycloaddition reactions has been reported for reactions catalyzed by chiral dirhodium(II,III) carboxamidates (Scheme 20) [103].…”
Section: Nitrones and Nitrile Oxidesmentioning
confidence: 97%
See 1 more Smart Citation
“…Enantioselective approaches involving transition metal catalysts have been successful with bidentate dipolarophiles such as those derived from oxazolidinones that provide two-point binding to the chiral Lewis acid [98]. However, there have been few examples of highly selective 1,3-dipolar cycloaddition reactions with α,β-unsaturated aldehydes that are monodentate dipolarophiles [8,[99][100][101][102], and those using methacrolein have shown greater selectivities than those with acrolein. A clear understanding of factors that influence reactivity and selectivity in nitrone cycloaddition reactions has been reported for reactions catalyzed by chiral dirhodium(II,III) carboxamidates (Scheme 20) [103].…”
Section: Nitrones and Nitrile Oxidesmentioning
confidence: 97%
“…These reactions [Scheme 21] are reported to occur quantitatively with high regioselectivity and stereocontrol [100]. The uses of chiral N,N 0 -dioxides for nitrone cycloaddition to alkylidene malonates [104] and to 3-arylidene-oxindoles [105] have been reported.…”
Section: Nitrones and Nitrile Oxidesmentioning
confidence: 98%
“…Unlike the last optimised reaction conditions described, the reactions carried out with a,b-unsaturated aldehydes 100 and nitrone 95 were better asymmetrically induced by chiral complex 80 (L = enal ligand), obtaining 3,4-endo-103 cycloadducts in very good yields and moderate to good enantioselections (Scheme 21, reaction c). 52 The chiral environment of complexes 79-83 ( Figure 7) was originated by the coordination with different diphosphanes, but the most synthetically useful complex was obtained when chiral 1,2-(diphenylphosphino) propane (R-Prophos) was employed (complexes 79 and 80). Interestingly, complexes 81-83 gave better results than catalysts 79 and 80 in the 1,3-DC was surveyed with nitrones 92b, and 95 with a variety of dipolarophiles.…”
Section: Nitronesmentioning
confidence: 99%
“…Interestingly, complexes 81-83 gave better results than catalysts 79 and 80 in the 1,3-DC was surveyed with nitrones 92b, and 95 with a variety of dipolarophiles. 52 An efficient regio-, diastereo-, and enantioselective transformation of several nitrones with allylic alcohols promoted by the chiral complex formed by diethylzinc and (R,R)-diisopropyl tartrate (DIPT) was achieved 84 (20 mol%, Figure 7). 53 In several examples, this reaction provided an approach to highly functionalised 3,5-transisoxazolidines with almost complete enantioselectivity (up to 83% yield and up to > 99% ee).…”
Section: Nitronesmentioning
confidence: 99%
“…A subsequent full study showed the efficiency and versatility of these complexes as catalysts for the reaction of diarylnitrones and α,β-unsaturated aldehydes [7,8]. Carmona's dicationic, half-sandwich, Rh and Ir aqua complexes containing diphosphine or PN ligands also proved good catalysts for this transformation [9][10][11][12]. The same group recently provided the first examples of asymmetric catalytic cycloaddition reactions of nitrones with methacrylonitrile [13].…”
Section: Introductionmentioning
confidence: 99%